The Introduction of Fluorine and Sulfur Atoms into Benzotriazole‐Based p‐Type Polymers to Match with a Benzotriazole‐Containing n‐Type Small Molecule: "The Same‐Acceptor‐Strategy" to Realize High Open‐Circuit Voltage. Issue 25 (22nd July 2018) - Tang, Ailing; Xiao, Bo; Chen, Fan; Zhang, Jianqi; Wei, Zhixiang; Zhou, Erjun
Abstract: "The Same‐Acceptor‐Strategy" (SAS) adopts benzotriazole (BTA)‐based p‐type polymers paired with a new BTA based non‐fullerene acceptor BTA13 to minimize the trade‐off between the open‐circuit voltage ( V OC ) and short circuit current ( J SC ). The fluorination and sulfuration are introduced to lower the highest occupied molecular orbitals (HOMO) of the polymers. The fluorinated polymer of J52‐F shows the higher power conversion efficiency (PCE) of 8.36% than the analog polymer of J52, benefited from a good balance between an improved V OC of 1.18 V and a J SC of 11.55 mA cm −2 . Further adding alkylthio groups on J52‐F, the resulted polymer, J52‐FS, exhibits the highest V OC of 1.24 V with a decreased energy loss of 0.48 eV, compared with 0.67 eV for J52 and 0.54 eV for J52‐F. However, J52‐FS shows an inferior PCE (3.84%) with a lower J SC of 6.74 mA cm −2, because the small Δ E HOMO between J52‐FS and BTA13 (0.02 eV) gives rise to the inefficient hole transfer and high charge recombination, as well as low carrier mobilities. The results of this study clearly demonstrate that the introduction of different atoms in p‐type polymers is effective to improve the SAS and realize the high ( V OC ) and PCE. Abstract : It is a large challenge to realize high performance organic solar cells with a high open‐circuit voltage ( V OC ) beyond 1.1 V . Here, "the Same‐Acceptor‐Strategy" containing benzotriazole (BTA)‐based p‐type polymer and a BTA based non‐fullerene acceptor (BTA13) is developed and a high efficiency of 8.36% with a V OC of 1.18 V is achieved by fluorinatedJ52‐F:BTA13 combination.